2019
DOI: 10.2139/ssrn.3416399
|View full text |Cite
|
Sign up to set email alerts
|

Requiem for a Nudge: Framing Effects in Nudging Honesty

Abstract: We examine framing effects in nudging honesty, in the spirit of the growing norm-nudge literature, by utilizing a high-powered and pre-registered study. Across four treatments, participants received one random truthful norm-nudge that emphasized 'moral suasion' based on either what other participants previously did (empirical message) or approved of doing (normative message) and varied in the framing (positive or negative) in which it was presented. Subsequently, participants repeatedly played the 'mind game' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 87 publications
5
32
0
Order By: Relevance
“…Existing work has shown that norm-based interventions such as norm-nudges need to be meticulously mapped onto the social environment in which they are implemented. Taking this into account, our results are also informative of ongoing scholarly debate on the reasons why prior studies that used such soft norm-nudge interventions had mixed success (Fellner et al, 2013;Castro and Scartascini, 2015;Hallsworth et al, 2017;Kettle et al, 2017;Dimant et al, 2020). For example, our findings suggest that norm-nudges exhibit the largest impact where preexisting norm perceptions are rather inconclusive (that is, where our norm-elicitation measure did not identify a uniquely prevailing norm, as in the Equity & NoInfo setting).…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…Existing work has shown that norm-based interventions such as norm-nudges need to be meticulously mapped onto the social environment in which they are implemented. Taking this into account, our results are also informative of ongoing scholarly debate on the reasons why prior studies that used such soft norm-nudge interventions had mixed success (Fellner et al, 2013;Castro and Scartascini, 2015;Hallsworth et al, 2017;Kettle et al, 2017;Dimant et al, 2020). For example, our findings suggest that norm-nudges exhibit the largest impact where preexisting norm perceptions are rather inconclusive (that is, where our norm-elicitation measure did not identify a uniquely prevailing norm, as in the Equity & NoInfo setting).…”
Section: Resultsmentioning
confidence: 56%
“…However, prior research has shown that the provision of norm information can -but does not necessarily have to -change the perception of social norms (for a recent example where this approach succeeded see Bursztyn et al, 2020b; and for where it didn't see Dimant et al, 2020). Thus, examining whether changes in the the punishment patterns are consistent with changes in social norms perceptions in our context is an empirical question.…”
Section: Experiments 2: Norm Information and Norm Perceptionmentioning
confidence: 83%
See 1 more Smart Citation
“…First of all, they provide a new example of a one-shot anonymous game in which nudging the injunctive norm has a significant effect. This is already a non-trivial result, since previous research has failed to find consistent and coherent evidence of a significant effect of nudging the injunctive norm on one-shot anonymous games: Bicchieri and Chavez (2010) found that manipulating the injunctive norm in the ultimatum game does have an effect, however Schram and Charness (2015) failed to show that manipulating the injunctive norm has an effect on the dictator game, and Dimant et al (2020) failed to successfully manipulate the injunctive norm in the mind game. This also opens a general question about which are the one-shot anonymous games where the injunctive norm plays a role and those where it does not, and why.…”
Section: Discussionmentioning
confidence: 93%
“…However, Schram and Charness (2015) failed to find a causal link between the injunctive norm and dictator game choices in anonymous games: they found that informing dictators about what other dictators think to be the right thing affects dictators' choices only when these choices are made public. Dimant, Van Kleef and Shalvi (2020) found that norm-based messages giving cues about the injunctive norm had no effect on honesty in a mind game, because, in their case, they failed to manipulate the norm. On the other hand, Bicchieri and Chavez (2010) manipulated the injunctive norm in variants of the ultimatum game and found that this does have an effect on proposers' offers.…”
Section: Introductionmentioning
confidence: 96%